The role of consumer confidence in forecasting consumption, evidence from Florida. (3rd September 2021) - Sandoval, Hector H.; Walsh, Anita N.
Abstract: Consumers' attitudes about the direction of the economy influence their decisions about discretionary purchases, saving, and investment. This paper uses data from Florida's consumer sentiment index to study the role and accuracy of consumer confidence in forecasting consumption, as well as the mechanism behind such a relationship. Spending on durable goods tends to be more discretionary in nature and it is frequently done using credit, thus potentially more sensitive to changes in consumer attitudes. Our results indicate that the in‐sample predictive power of the index and its questions is limited to predicting spending on durable goods, particularly, on autos. Furthermore, consumer confidence does not improve the out‐of‐sample forecast beyond the forecast from a baseline model, which considers economic fundamentals. Finally, the evidence shows that the relationship between shocks in consumer confidence and economic activity arises because confidence measures contain information about the state of the economy, thus rejecting animal spirits.